2021
DOI: 10.1016/j.ccell.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibrutinib with R-CHOP chemotherapy in genetic subtypes of DLBCL

Abstract: Highlights d BTK inhibitor ibrutinib plus R-CHOP is effective in younger patients with ABC DLBCL d Genetic subtypes of DLBCL differ in genotype, phenotype, and oncogenic mechanisms d MCD and N1 subtypes acquire mutations that promote chronic active BCR signaling d Patients with the MCD and N1 subtypes have 100% survival with ibrutinib plus R-CHOP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
145
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 90 publications
1
145
0
2
Order By: Relevance
“…Very recently, after analysis of biopsies from Phoenix trial, Wilson. et al reported that the 3-year event-free survival of younger patients treated with ibrutinib plus R-CHOP was 100% in the MCD subtypes, which provide solid evidence of the efficacy of ibrutinib in DLBCL (3) .…”
Section: Introductionmentioning
confidence: 95%
“…Very recently, after analysis of biopsies from Phoenix trial, Wilson. et al reported that the 3-year event-free survival of younger patients treated with ibrutinib plus R-CHOP was 100% in the MCD subtypes, which provide solid evidence of the efficacy of ibrutinib in DLBCL (3) .…”
Section: Introductionmentioning
confidence: 95%
“…In a retrospective analysis of PHOENIX trial biopsies, Wilson et al (2021) investigated the presence of DLBCL genetic subtypes to further explore this finding [ 18 ]. Investigators found that survival benefit among patients receiving ibrutinib + R-CHOP was more pronounced within specific genetic subtypes (MCD and N1) [ 18 , 19 ], common in younger patient participants with ABC-COO.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis of PHOENIX trial biopsies, Wilson et al (2021) investigated the presence of DLBCL genetic subtypes to further explore this finding [ 18 ]. Investigators found that survival benefit among patients receiving ibrutinib + R-CHOP was more pronounced within specific genetic subtypes (MCD and N1) [ 18 , 19 ], common in younger patient participants with ABC-COO. These findings offer preliminary evidence of a biological mechanism for the increased benefit of ibrutinib for patients under 60 with specific genetic subtypes common among the ABC subtype of DLBCL [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations